Plant diversity in Montel Muria Kudus Waterfall area for college student e-module development - Venty Zuslia; Agung Wijaya Subiantoro (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Many college students have difficulty in understanding the diversity and morphology of plants at the species level. The research aims to analyze the potential of species-level plant diversity in Montel Muria Kudus Waterfall, develop e-modules integrating local potential, and preserve the local potential of Montel Muria Kudus Waterfall. The research and development study design with the 4D model was implemented in this study to produce the e-module. E-module was tested on 30 Tadris Biology college students who assigned with random sampling technique. Data were collected with expert validations and trial. In Montel Muria Kudus Waterfall, various plant species groups were found, including ferns, epiphytes, shrubs, herbs, and trees. Instructional media expert validation obtained score of 95% which in the “very valid” category. Moreover, material experts scored of 91.66%, means in the “very valid” category. Practical feasibility analysis obtained score of 95.83%, represents the “very practical” category. The results of the college students’ N-Gain value of 56.7338, represents the category of “moderately effective” in improving science literacy. This research findings show that the e-module produced can potentially be widely implemented in biology instruction for improving college students’ science literacy skill as well as preserving local potential.